2017
DOI: 10.20892/j.issn.2095-3941.2017.0061
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of Wnt/β-Catenin signal inhibitor TMEM88 is associated with unfavorable prognosis of non-small cell lung cancer

Abstract: Objective: Recent research has indicated that altered promoter methylation of oncogenes and tumor suppressor genes is an important mechanism in lung cancer development and progression. In this study, we investigated the association between promoter methylation of TMEM88, a possible inhibitor of the Wnt/β-Catenin signaling, and the survival of patients with non-small cell lung cancer (NSCLC). Methods: Twelve pairs of tumor and adjacent non-tumor samples were used for microarray analyses of DNA methylation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…TMEM88 was first identified in silico as a PDZ-domain-binding protein (Lee et al., 2010), based on the presence of a VWV motif that was known to interact with DVL. This led naturally to the investigation of its ability to modulate Wnt signaling, which was confirmed in reporter assays (Lee et al., 2010), of potential significance given the association of TMEM88 expression patterns described in various human neoplasias (Ma et al., 2017, Yu et al., 2015, Zhang et al., 2015). However, whether the impact of TMEM88 on Wnt signaling is actually mediated through interaction with DVL had not been previously tested.…”
Section: Discussionmentioning
confidence: 94%
“…TMEM88 was first identified in silico as a PDZ-domain-binding protein (Lee et al., 2010), based on the presence of a VWV motif that was known to interact with DVL. This led naturally to the investigation of its ability to modulate Wnt signaling, which was confirmed in reporter assays (Lee et al., 2010), of potential significance given the association of TMEM88 expression patterns described in various human neoplasias (Ma et al., 2017, Yu et al., 2015, Zhang et al., 2015). However, whether the impact of TMEM88 on Wnt signaling is actually mediated through interaction with DVL had not been previously tested.…”
Section: Discussionmentioning
confidence: 94%
“…The increase in membrane-associated TMEM88 expression also led to a decrease of proliferation, colony formation, migration and invasion and to a decrease in tumor growth in vivo highlighting the tumor suppressor role of TMEM88 when it is localized to the membrane of the cell. Furthermore, TMEM88 promoter methylation is associated with unfavorable prognosis in NSCLC (Ma et al, 2017). On the contrary, its cytosolic localization is correlated with a low level of differentiation of the tumor and poor prognosis of patients with NSCLC.…”
Section: Part 2: Tmems As Oncogenesmentioning
confidence: 99%
“…Metastasis is the major cause of the poor prognosis of NSCLC ( 48 ). Accumulating evidence has revealed that multiple TMEM proteins, such as TMEM209A ( 19 ), TMEM88 ( 20 , 21 ), TMEM106A ( 22 ), TMEM17 ( 23 ), TMEM98 ( 49 ) and TMEM48 ( 50 ), can serve as prognostic markers for NSCLC. In the present study, survival analysis using the Kaplan-Meier Plotter online bioinformatics datasets revealed that patients with low TMEM229A expression had a poorer prognosis compared with those with high TMEM229A expression, suggesting that TMEM229A could be considered as a prognostic marker for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TMEM209, localized to the nuclear envelope and in the cytoplasm of lung cancer cells, is upregulated in lung cancer and promotes cell proliferation and tumor progression by interacting with nucleoporin 205 kDa ( 19 ). TMEM88 is a Wnt regulatory protein, and its cytosolic form and the methylation of TMEM88 are highly expressed in lung cancer, which accelerates the tumorigenesis and progression of lung cancer ( 20 , 21 ). Moreover, Liu and Zhu ( 22 ) reported that TMEM106A was lowly expressed in NSCLC and suppressed cell proliferation, migration and invasion, as well as induced cell apoptosis via the PI3K/AKT/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%